bel-, pe-, me- Upaya Peningkatan Hasil Belajar Peserta Didik Kelas VIII SMP PGRI 1 Denpasar Pada Mata Pelajaran Pendidikan Agama Hindu dan Budi Pekerti Melalui Penerapan Soal HOTS - Ni Kadek, Hari Sitaresmi; I Gusti Ngurah , Agung Wijaya Mahardika; Ni Nyoman, Yunike Kurniarini (UHN IGB Sugriwa Denpasar, 2024)
This research discusses about the best steps to implement HOTS (Higher Order Thinking Skill) questions in an attempt to improve the learning outcomes of grade eight students at SMP PGRI 1 Denpasar in the subjects of Hindu Religious Education and Character. This research aims to apply HOTS (Higher Order Thinking Skill) question-based assessment so that it can improve and increase the learning outcomes of grade eight students at SMP PGRI 1 Denpasar. This research is Participant Classroom Action Research (CAR), so that in this research the researcher plays a full role and is involved directly in the research process from start to finish. The CAR model that used in this research is the CAR model by Kemmis and Mc. Taggart which is a development of the Kurt Lewin models. As a result, the average score obtained was 63 and the percentage of completeness of learning outcomes during the pre-cycle was 33%, which increased in the first cycle with the step of implementing HOTS (Higher Order Thinking Skill) questions integrated with scientific learning models and group discussion methods, obtaining an average score. amounted to 74 and the percentage of completeness of learning outcomes was 62%. The final improvement in the second cycle with the step of implementing HOTS (Higher Order Thinking Skill) questions integrated with the gamification learning model and group discussion method obtained an average score of 85 and a percentage of complete learning outcomes of 86%. In conclusion, the best steps to implement HOTS (Higher Order Thinking Skill) questions in an attempt to improve the learning outcomes of class VIII students at SMP PGRI 1 Denpasar, Hindu Religious Education and Character Education subjects are the implementation of the steps in the second cycle, which integrate questions HOTS (Higher Order Thinking Skill) with a gamification model and group discussion method. Future researchers are advised to analyze the limitations of this research, so that this research can be developed.